Interaction of γ-Polyglutamic Acid/Polyethyleneimine/Plasmid DNA Ternary Complexes with Serum Components Plays a Crucial Role in Transfection in Mice - Tomotaka Ko; Shintaro Fumoto; Tomoaki Kurosaki; Moe Nakashima; Hirotaka Miyamoto; Hitoshi Sasaki; Koyo Nishida (MDPI AG, 2024)
Typical examples of non-viral vectors are binary complexes of plasmid DNA with cationic polymers such as polyethyleneimine (PEI). However, problems such as cytotoxicity and hemagglutination, owing to their positively charged surfaces, hinder their in vivo use. Coating binary complexes with anionic polymers, such as γ-polyglutamic acid (γ-PGA), can prevent cytotoxicity and hemagglutination. However, the role of interactions between these complexes and serum components in in vivo gene transfer remains unclear. In this study, we analyzed the contribution of serum components to in vivo gene transfer using PEI/plasmid DNA binary complexes and γ-PGA/PEI/plasmid DNA ternary complexes. In binary complexes, heat-labile components in the serum greatly contribute to the hepatic and splenic gene expression of the luciferase gene. In contrast, serum albumin and salts affected the hepatic and splenic gene expression in the ternary complexes. Changes in physicochemical characteristics, such as increased particle size and decreased absolute values of ζ-potential, might be involved in the enhanced gene expression. These findings would contribute to a better understanding of in vivo non-viral gene transfer using polymers, such as PEI and γ-PGA.